Queer Rural Space in Early Twenty-First Century American Narrative: Listing Landscapes in George Hodgman,Ocean Vuong, and Louis Ceci - Parker, Joshua (AmLit)
"Ruralism" in recent American narratives by queer authors is discussed here as a series of engagements and withdrawals from small-town socio-political landscapes, ensconced in US literature from early US realism and modernism, by contemporary focalizers, who are positioned as quasi-outsiders in the wake of post-industrial withdrawal. The essay pinpoints narrative prose and verse published in the second and third decades of the twenty-first century: George Hodgman's Bettyville (2015), a memoir exploring recovery from addiction, Midwestern childhood, aging, gay identity, and rural climate change; Ocean Vuong's novel On Earth We're Briefly Gorgeous (2019), describing migrant work patterns and sexuality in central Connecticut; and Louis Ceci's multi-generational Croy Cycle novels (2008-2022) set in small-town Oklahoma.